Simulasi Pembuatan Jaringan Peer To Peer Menggunakan Cisco Paket Tracer - Ratnasari Ratnasari; Selpi Amanda Fadillah; Rahima Mahabbah; Ismah Nurul Sya’bani; Alfi Manarul Huda; Didik Aribowo (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Data communication is a field of science that studies the process of sending data, as well as how data can be received from sending and receiving terminals. A computer network is a set of "interconnections" between 2 or more autonomous computers connected by cable or wireless transmission media. Cisco packet tracer is a network simulation application developed by Cisco as a simulator as a learning medium for Cisco devices. Peer-to-Peer (P2P) network simulation using Cisco Packet Tracer software is an effective method for understanding, designing, and analyzing P2P networks in a controlled environment. The method used is literature study and carrying out simulation practice on Cisco Packet Tracer software to simulate a network. This research method aims to outline the steps and procedures required to simulate a Peer-to-Peer (P2P) network using Cisco Packet Tracer software. This abstract presents a brief view of the simulation approach used to model and examine the performance of a P2P network using Cisco Packet Tracer contains implementation steps for peer to peer network simulation. Through simulation, in-depth performance analysis can be carried out on various aspects of P2P networks, such as throughput, latency and reliability. This allows researchers and practitioners to understand how P2P networks behave under various conditions. Thus, P2P network simulation with Packet Tracer provides a useful tool for researchers and practitioners to understand and optimize P2P network performance in various scenarios.